2003
DOI: 10.1210/me.2001-0035
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Receptor Subtype 5 Regulates Insulin Secretion and Glucose Homeostasis

Abstract: Somatostatin (SRIF) regulates pancreatic insulin and glucagon secretion. In the present study we describe the generation of SRIF receptor subtype 5 knockout (sst(5) KO) mice to examine the role of SRIF receptor subtypes (sst) in regulating insulin secretion and glucose homeostasis. Mice deficient in sst(5) were viable, fertile, appeared healthy, and displayed no obvious phenotypic abnormalities. Pancreatic islets isolated from sst(5) KO mice displayed increased total insulin content as compared with islets obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 59 publications
12
97
0
1
Order By: Relevance
“…This study also demonstrated that the deletion of A c c e p t e d M a n u s c r i p t 14 SSTR2 leads to the loss of moderate insulinostatic activity of the SSTR2-agonist, suggesting that at higher concentrations an SSTR2-agonist could interfere with other SSTRs (at 100 nM). The SSTR-multireceptor theory as regulators of murine insulin secretion was confirmed using islets lacking the SSTR5 gene (Strowski et al, 2003). In these SSTR5-deficient islets the insulinostatic activities of both SST-28 and a SSTR5-selective agonist were markedly attenuated, but not completely lost.…”
Section: In Vitro Studiesmentioning
confidence: 88%
See 2 more Smart Citations
“…This study also demonstrated that the deletion of A c c e p t e d M a n u s c r i p t 14 SSTR2 leads to the loss of moderate insulinostatic activity of the SSTR2-agonist, suggesting that at higher concentrations an SSTR2-agonist could interfere with other SSTRs (at 100 nM). The SSTR-multireceptor theory as regulators of murine insulin secretion was confirmed using islets lacking the SSTR5 gene (Strowski et al, 2003). In these SSTR5-deficient islets the insulinostatic activities of both SST-28 and a SSTR5-selective agonist were markedly attenuated, but not completely lost.…”
Section: In Vitro Studiesmentioning
confidence: 88%
“…The results of these studies indicate that SSTR1, SSTR2 and SSTR5 regulate murine insulin secretion. While the residual activity of the SSTR5-selective agonist (Berk et al, 1999;Rohrer et al, 1998;Rohrer and Schaeffer 2000) on insulin secretion from SSTR5-deficient islets (Strowski et al, 2003) could be explained by an interaction with the SSTR1 (only 10-fold selectivity). Collectively, there are several important findings originating from the studies mentioned above that could be possibly explained by the ability of SSTRs to interact with each other.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, dopamine receptors are able to homodimerize (47,48) and heterodimerize (49) with members of the same family or with another type of receptors. For instance, somatostatin type 5 receptors, which contribute to the regulation of glucose homeostasis and insulin sensitivity (50), can heterodimerize with D2 receptors, thereby enhancing functional activity (51). Therefore, in the context of insulin secretion, dopamine receptors could interact with somatostatin receptors known to be present in beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cloning of the receptors promoted the development of specific SRIF ligands, agonists and antagonists (Rohrer et al, 1998;Bass et al, 1996;Reubi et al, 2000;Hoyer et al, 2004;Tulipano et al, 2002), specific antibodies and genetically modified mice (Kreienkamp et al, 1999;Viollet et al, 2000;Allen et al, 2003;Strowski et al, 2003) An extensive number of studies and a number of reviews Patel 1999;Tannenbaum and Epelbaum, 2000;Csaba and Dournaud, 2001;Olias et al, 2004) have addressed the intracellular signalling pathways responsible for SRIF's diverse actions. The results obtained were mostly from studies performed in cell lines transfected with the recombinant receptors, but also in native systems.…”
Section: Introductionmentioning
confidence: 99%